The Fowl twins - Colfer, Eoin (Los Angeles ; New York : Disney HYPERION, 2019)
Eleven-year-old twins Miles and Beckett Fowl enjoy adventure and mayhem while helping a troll escape nefarious forces that want his magic.
Keywords: Adventure and adventurers -- Fiction; Magic -- Fiction; Twins -- Fiction; Brothers -- Fiction; Trolls -- Fiction